Digital Environments : Ethnographic Perspectives Across Global Online and Offline Spaces - Urte Undine Frömming; Steffen Köhn; Samantha Fox; Mike Terry (transcript, 2017)
Digital technology permeates the physical world. Social media and virtual reality, accessed via internet capable devices – computers, smartphones, tablets and wearables – affect nearly all aspects of social life.The contributions to this volume apply innovative forms of ethnographic research to the digital realm. They examine the emergence of new forms of digital life, such as political participation through comments on East Greenlandic news blogs, the personal use of video broadcasting applications, the rise of transnational migrant networks facilitated by social media, or the effects of Facebook, Twitter, and Instagram on global conflicts.